Simple Project Based Learning To Improve Pronunciation Element In Teaching Speaking - Muhammad Husnu; Ahmad Yusri; Abdurrofi Daman Huri (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
The purpose of this research is to improve students' speaking skills through a project based learning, making them more immersive and active. This study used experimental techniques and analysis of students' cognitive abilities with quantitative research techniques through oral tests. The research questions considered in this study are: was there a significant effectiveness of simple project-based learning syntaxes in teaching speaking (pronunciation element) and to what extent was the effectiveness of simple project-based learning syntaxes in teaching speaking (pronunciation element)?. The purpose of this study is to know whether the Simple project-based learning syntaxes to teach speaking (pronunciation element) contributes significantly to the senior high school students’ speaking ability of eleventh grade student of MA NW Juet academic year 2024. And the perpose of this research is to find out the extent of Simple project-based learning syntaxes in teaching speaking (pronunciation element). The analytical methods used for data processing are included in the Social Science Statistics 22.0 for Windows. The results before applying the project based learning technique, only 50% of students are able to spek in English and after applying the project based learning, it improved student's ability to speak in English by 80%. Applying project based learning , especially speaking, This is the right strategy to improve students' speaking skills (pronunciation).